(untitled) (Scientific journal of the Fergana State University, 2025)
This article examines the theoretical and methodological foundations for researching social modernization processes, provides a philosophical analysis of these processes, and explores their strategic significance. Additionally, the philosophical characteristics of social modernization processes are analyzed.